SMART ENVIRONMENT: ANALYSIS OF WATER MANAGEMENT POLICY IN MAKASSAR - Misbahuddin, Angga - (Fakultas Politik Pemerintahan IPDN, 2023)
Abstract This article aims to analyze the Makassar government's policies on clean water management in Makassar, one of Indonesia's major cities. Utilizing the concept of a smart environment as an analytical framework, this study investigates whether Makassar's clean water management aligns with the principles of a smart environment. The escalating construction of apartments and hotels has notable consequences for water resources in Makassar. Simultaneously, the city experiences rapid population growth each year, indirectly affecting clean water consumption. This qualitative study employs descriptive analysis, aiming to elucidate and depict the current events concerning the research object. Secondary data forms the basis of this study. Research findings indicate that Makassar's clean water management does not conform to the smart environment concept. This discrepancy can be attributed to inconsistent clean water distribution aggravated by the city's swiftly growing population. Furthermore, the implementation of smart environment principles in managing clean water resources, such as the development of Public Green Open Spaces, waste management, river revitalization, and slum settlement management, remains suboptimal. These aspects significantly impact the establishment of a smart environment, particularly concerning the universal provision of clean water for Makassar's residents. Keywords: Makassar City, smart environment, policy, water management